Considerations In Training On-The-Job Trainers - Bill Wiehagen; Don Conrad; Tom Friend; Lynn Rethi (The National Institute for Occupational Safety and Health (NIOSH), 2002)
On-the-job training (OJT) is a very common method of teaching job skills. Much of the training is done by experienced workers. This paper discusses small investments that can help improve the effectiveness of OJT. Effective OJT involves some structure and planning in the transfer of responsibility for task performance from the trainer to the novice. Assisting the OJT trainer could involve helping develop up-to-date job analyses and offering strategies for teaching and evaluating job skills. The scope of this paper addresses (1) organizational considerations supporting structured OJT, (2) general strategies for structuring OJT, (3) a typical approach for conducting OJT, (4) characteristics and duties of OJT trainers, and (5) limitations of OJT as a teaching method. Health, safety, and operational skills can be connected through training. Haul truck operator training is used to illustrate some of the concepts discussed in this paper.